Pragmatics in EFL teaching building meaning beyond words through the use of videos - Olivares, Cinthya (2016)
Pragmatics, a seemingly unexplored area by most EFL teachers nowadays, offers a number of language competencies in order to convey and understand meaning successfully. It is worth mentioning that an EFL setting does not usually provide the same availability of opportunities to practice pragmatics as an ESL setting does. Thus, contextual cues, for this particular study, will be provided by audio-visual aids. This authentic material certainly displays the connotative meaning of words and phrases and the degree of appropriateness that have currently been downplayed in EFL scenarios by the over teaching of syntactic knowledge, mostly. Grounded on these premises, this qualitative study emerged. It was conducted with freshman and junior students of the English majors at Universidad Nacional of Costa Rica, Brunca Branch as an attempt at identifying the treatment pragmatics has received in the oral expression courses, and devising several techniques on how to help students grasp the connotative meaning of words and phrases derived from contextual factors found in authentic audio-visual aids.